Eddies in the Hawaiian Archipelago Region: Formation, Characterization, and Potential Implications on Larval Retention of Reef Fish. Issue 5 (16th May 2020) - Lindo‐Atichati, David; Jia, Yanli; Wren, Johanna L. K.; Antoniades, Andreas; Kobayashi, Donald R.
Abstract: Here we present an assessment of eddy activity in a 3, 500 × 2, 000 km region of the North Pacific. Eddies were identified and tracked within a numerical simulation that used the Massachusetts Institute of Technology general circulation model and an eddy characterization algorithm. Spatially, eddy births were more frequent: (1) nearshore (cyclones) and offshore (anticyclones) on the windward side of the main Hawai'ian Islands; (2) in patches of cyclones and anticyclones that resembled the dipole structure of wind stress curl along the islands' leeward side; and (3) in zonal patches of eddies of both polarities west and north of the islands. Temporally, high eddy activities occurred in spring. There was a meridional distribution of eddy lifespans, which increased northward. Cyclones were more abundant, longer‐lived, smaller, and more nonlinear. Reef fish spawning locations in Hawai'i coincide with the regions of high eddy activity, with nonlinear eddies responsible for high larval retention. Plain Language Summary: It has been well documented that rotating bodies of water—the so‐called cyclonic and anticyclonic eddies—heavily influence biological productivity in the North Pacific. However, the dynamics of eddy formation and activity are not always clear, often lacking spatial resolution and statistical evaluation. Here we used a general circulation model and an eddy detection tool to provide a comprehensive description of ocean eddies in a 3, 500 × 2, 000 km region of the North Pacific. Our analysis revealed seasonality in eddy genesis for the whole region, with more eddies forming in spring. Eddy generation west of the Big Island of Hawai'i is consistent with the mechanism of formation by the strong dipole of wind stress curl. Notably, there are marked spatial patterns of eddy rotations, sizes, propagation speeds, and lifespans on both sides of the main Hawai'ian Islands. This work also sheds light on the linkages between eddy activity and retention of larval fish in the Hawai'ian Archipelago. Spawning sites of coral reef fish in Hawai'i coincide with most of the regions of high eddy activity. Interestingly, regardless of eddy polarity, nonlinear slow‐propagating (fast swirling) eddies enhance larval retention while linear fast‐propagating (slow‐swirling) eddies enhance larval export and eventually larval dispersion. Key Points: Eddy generation in the North Pacific is highest in spring and lowest in fall except for the regions alongside the main Hawaiian Islands Mean anticyclone eddy intensity is significantly weaker than cyclone eddy intensity Regardless of eddy polarity, nonlinear (linear) eddies enhance larval retention (export) in island population of coral reef fish